Introduction to general, organic and biochemistry - Bettelheim, Frederick A.; Brown, William H. ;Campbell, Mary K. ;Farrell, Shawn O. ;Torres, Omar J. (Singapore : Cengage Learning Asia Pte Ltd, 2014)
Gain a comprehensive understanding of chemistry and see how it relates to health science with INTRODUCTION TO GENERAL, ORGANIC, AND BIOCHEMISTRY. This bestseller features dynamic art, interesting examples, coverage of the latest issues, and a wide variety of medical and biological applications. As you explore topics such as botulin toxin as a cosmetic agent, implications for the use of antibiotics, and ultraviolet sunscreen, you will see how useful the study of chemistry is to your life. The book's built-in integration with OWLv2 (Online Web Learning) turns your chemistry study time into active experiences that build your comprehension, bring concepts to life, and help you succeed in the course.
1. Matter, Energy, and Measurement. -- 2. Atoms. -- 3. Chemical Bonds. -- 4. Chemical Reactions. -- 5. Gases, Liquids, and Solids. -- 6. Solutions and Colloids. -- 7. Reaction Rates and Chemical Equilibrium. -- 8. Acids and Bases. -- 9. Nuclear Chemistry. -- 10. Organic Chemistry. -- 11. Alkanes. -- 12. Alkenes and Alkynes 13. Benzene and Its Derivatives -- 14. Alcohols, Ethers, and Thiols. -- 15. Chirality: The Handedness of Molecules. -- 16. Amines.-- 17. Aldehydes and Ketones. -- 18. Carboxylic Acids. -- 19. Carboxylic Anhydrides, Esters, and Amides. -- 20. Carbohydrates. -- 21. Lipids. -- 22. Proteins. -- 23. Enzymes. -- 24. Chemical Communications: Neurotransmitters and Hormones.-- 25. Nucleotides, Nucleic Acids, and Heredity. -- 26. Gene Expression and Protein Synthesis. -- 27. Bioenergetics: How the Body Converts Food to Energy. -- 28. Specific Catabolic Pathways: Carbohydrate, Lipid, and Protein Metabolism. -- 29. Biosynthetic Pathways. -- 30. Nutrition. -- 31. Immunochemistry -- 32. Body Fluids. -- Appendix I. Exponential Notation. -- Appendix II. Significant Figures. -- Answers to In-Text and Odd-Numbered End-of-Chapter Problems. -- Glossary -- Index.
"3rd Philippine reprint 2016"--Title page verso "This edition is reprinted with license from Brooks Cole, a part of Cengage Learning, for sale in the Philippines only."--Title page verso
Includes index.
Keywords: CHEMISTRY -- TEXTBOOKS